Determining the Effects of Emotional Freedom Techniques on Sexual Dysfunction and Self‐Care Management in Women Diagnosed With Multiple Sclerosis - Ayşe Çuvadar; Ayfer Güneş; Yeter Çuvadar Baş; Sezgin Kehaya (Brain and Behavior, 2025)
ABSTRACT Aim This study aims to determine the effects of Emotional Freedom Techniques (EFT) on sexual dysfunction and self‐care in women diagnosed with multiple sclerosis (MS). Method This study was conducted using a pretest–posttest experimental design, including follow‐up assessments to evaluate the sustainability of the intervention effects. The sample consisted of 16 women aged between 19 and 49 years who were diagnosed with MS and presented to the neurology clinic of a university hospital in Türkiye between October 2023 and September 2024. Data collection instruments included the Personal Information Form (PIF), Multiple Sclerosis Intimacy and Sexuality Questionnaire‐19 (MSISQ‐19), and Self‐Care Management Process in Chronic Illness (SCMP‐G). Repeated measures analysis of variance (ANOVA) was employed to analyze changes in sexuality and self‐care over time. Statistical significance was set at p < 0.05. Results Participants received two EFT sessions per month, each lasting 60 min, together with affirmation sessions conducted at least twice a week for 10–15 min. The mean scores of all subdimensions of the MSISQ‐19 reached the lowest levels by the seventh week following EFT intervention, with significant differences between time points (p < 0.05). Even though an improvement was observed in the social protection dimension of self‐care, the mean scores for the self‐protection subdimension decreased. Conclusion The application of EFT demonstrated positive effects on sexual functioning and self‐care levels in women with MS. Therefore, EFT can be integrated into the holistic care processes of patients with MS.